PtosisDiffusion: a training-free workflow for precisely predicting post-operative appearance in blepharoptosis patients based on diffusion models - Huang, Shenyu; Xie, Jiajun; Yang, Boyuan; Gao, Qi; Ye, Juan (Frontiers in Cell and Developmental Biology, 2024)
PurposeThis study aims to develop a diffusion-based workflow to precisely predict postoperative appearance in blepharoptosis patients.MethodsWe developed PtosisDiffusion, a training-free workflow that combines face mesh with ControlNet for accurate post-operative predictions, and evaluated it using 39 preoperative photos from blepharoptosis patients. The performance of PtosisDiffusion was compared against three other diffusion-based methods: Conditional Diffusion, Repaint, and Dragon Diffusion.ResultsPtosisDiffusion demonstrated superior performance in subjective evaluations, including overall rating, correction, and double eyelid formation. Statistical analyses confirmed that PtosisDiffusion achieved the highest overlap ratio (0.87 ± 0.07) and an MPLPD ratio close to 1 (1.01 ± 0.10). The model also showed robustness in extreme cases, and ablation studies confirmed the necessity of each model component.ConclusionPtosisDiffusion generates accurate postoperative appearance predictions for ptosis patients using only preoperative photographs. Among the four models tested, PtosisDiffusion consistently outperformed the others in both subjective and statistical evaluation.